Escalation of Anglo-German Relations Amidst Strengthening of ‘War Party’ in Germany during Crisis Period of 1908—1911 - A. A. Egorov; O. O. Boyko (Научный диалог)
The subject of the study is Anglo-German relations during the crisis period of 1908-1911. The aim of the work is to examine the views and activities of German state and public figures who directly or indirectly influenced the overall background of Anglo-German relations in the context of escalating antagonism between the two states. This process was influenced by the so-called ‘war party’, to which a certain group of German politicians with pronounced nationalist-chauvinistic ideals belonged. The historical sources used in the article are analyzed from a personal approach and anthropology of international relations. Based on these sources, the previously poorly studied activities of the German elite, who acted in conjunction with Kaiser Wilhelm II and shaped Germany’s current foreign policy agenda in the pre-war period, are characterized. The author concludes that throughout the entire crisis period of Anglo-German relations from 1908 to 1911, neither the German Ministry of Foreign Affairs nor Chancellors B. Bülow and T. Bethmann-Hollweg were able to fully seize the initiative from the ‘war party’, which was shaping Wilhelm II’s policies. This became possible due to constitutional deformation and the celebrated ideas of a great national state in German society.